2017
DOI: 10.4103/2231-0770.197512
|View full text |Cite
|
Sign up to set email alerts
|

Very severe spinal muscular atrophy (Type 0)

Abstract: This case report describes a rare phenotype of very severe spinal muscular atrophy (SMA) in a newborn who presented with reduced fetal movements in utero and significant respiratory distress at birth. The patient was homozygously deleted for exon 7 and exon 8 of the survival motor neuron gene 1. Very severe SMA should be considered in the differential diagnosis of respiratory distress at birth, and more research should be dedicated to investigate the genetic determinants of its widely variable phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Symptoms of the most severe forms of SMA (types 0 and I) appear from the late prenatal period to the early postnatal period. [4][5][6] Martínez-Hernández et al 22 reported a prenatal delay of muscle maturation in SMA that emphasizes the importance of initiating treatment as early as possible. Therefore, we investigated the applicability of fetal gene therapy for the prevention of SMA symptoms using a mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of the most severe forms of SMA (types 0 and I) appear from the late prenatal period to the early postnatal period. [4][5][6] Martínez-Hernández et al 22 reported a prenatal delay of muscle maturation in SMA that emphasizes the importance of initiating treatment as early as possible. Therefore, we investigated the applicability of fetal gene therapy for the prevention of SMA symptoms using a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of the most severe forms of SMA (types 0 and I) appear from the late prenatal to the early postnatal period and include: decreased movement at prenatal stage, fetal akinesia sequence, congenital contractures, and postnatal respiratory insufficiency. [4][5][6] Fetal gene therapy presents as a promising approach to prevent irreversible tissue damage caused by early onset genetic disorders that require early childhood treatments, such as SMA, Duchenne muscular dystrophy (DMD), CF, and lysosomal storage diseases. Restoring the defective gene function at an older age is only capable of halting progression of the disease but is not generally able to reverse the pathological alterations and, therefore, cannot provide complete cures for these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The copy number of SMN2 gene modifies the severity of the disease phenotype as a high number of SMN2 copies is related to milder phenotypes [40,42]. For instance, SMA type I patients generally have one or two SMN2 copies, while SMA type III/IV patients have more than four copies [43,44]. Nevertheless, this inverse relationship is not always true, as a few patients with two SMN2 copies showed milder SMA phenotypes, while there have also been patients with three SMN2 copies that have been defined as type I [21,[45][46][47].…”
Section: Disease Etiologymentioning
confidence: 99%
“…SMA is divided to 4 types based on the age of onset and maximum motor function achieved. SMA type 1 includes very weak infants with reduced fetal movements in utero, inability to sit independently and short survival time (102,104). Type 2 of SMA includes non-ambulant patients able to sit but unable to walk independently, while SMA type 3 refers to ambulant patients with childhood onset of disease (102).…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%